Obstetric and Neonatal Outcome of Pregnancy in Carney Complex: A Case Report - Ralser, Damian J.; Strizek, Brigitte; Kupczyk, Patrick; Stoffel-Wagner, Birgit; Altengarten, Julia; Müller, Andreas; Woelfle, Joachim; Gembruch, Ulrich; Klingmueller, Dietrich; Merz, Waltraut M.; Paschkowiak-Christes, Anke (Frontiers in Endocrinology, 2020)
Background: Carney complex (CNC) is a rare multiple endocrine neoplasia syndrome with autosomal dominant inheritance. Affected individuals present with mucocutaneous lentigines/blue nevi, cardiac and noncardiac myxomatous tumors, and multiple endocrine tumors. Mutations in PRKAR1A have been identified as genetic cause of the disease. Here, we report on pregnancy, delivery and puerperium in a woman with genetically confirmed CNC and her newborn. Case: The 31 year-old gravida 5 para 1 with CNC was referred at 26 weeks of gestation. Adrenocorticotropin-independent hypercortisolism, hyperglycemia, hypertension, low serum potassium, and osteoporotic fractures were present. Treatment with metyrapone, a reversible 11-beta-hydroxylase inhibitor, was initiated. The maternal condition improved, and a five weeks’ pregnancy prolongation could be achieved. Elective repeat cesarean section was performed at 31 weeks of gestation for recurrent vaginal bleeding. The neonate developed transient hyponatremia necessitating hydrocortisone substitution for two weeks. Conclusion: In our case, treatment of CNC-associated hypercortisolism in pregnancy with metyrapone was effective. Maternal side effects did not occur. The newborn presented with transient hypocortisolism most likely due to transplacental drug effect. Our case illustrates that the treatment of rare diseases in pregnancy represents a challenge requiring interdisciplinary team work.